Serum IL-17 and postmenopausal osteoporosis - AL-Tai, Tharwa H. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: Osteoporosis is a bone condition that makes bones thininer and more fragile because of reduced bone density and it puts people at risk of fractures, especially of the hip, spinal vertebrae and wrist. Objective: This study will highlighted the role of IL-17 in postmenopausal osteoporosis. Patients and methods: This study applied on 84 includes subjects (42 postmenopausal osteoporosis patient and 42 of healthy control group), conducted from December 2014 to March 2015 to measure the IL-17 serum level by using ELISA kit. Results: In osteoporotic postmenopausal women the mean of serum IL-17 was (0.49pg/ml) and it is significantly higher than that of healthy group (0.09pg/ml). Conclusion: Serum IL-17 was significantly elevated in osteoporotic postmenopausal women when compared to healthy postmenopausal women.